Cardiovascular Medical Education During the Coronavirus Disease 2019 Pandemic: Challenges, Adaptations, and Considerations for the Future - Hilary Shapiro; Nosheen Reza (US Cardiology Review)
The coronavirus disease 2019 (COVID-19) pandemic has greatly impacted graduate medical education for cardiovascular fellows in training. During the initial case surge in the US in early 2020, most training programs reformatted didactic curricula, redeployed fellows in training to non-cardiac services or furloughed fellows in training on non-essential services, reimagined procedural training in light of decreased case volumes, and balanced issues regarding trainee wellbeing and safety with occupational COVID-19 exposure risk. In this article, the authors review the educational challenges posed by the COVID-19 pandemic, and discuss opportunities to incorporate technological and curricular innovations spurred by the pandemic into cardiovascular fellowship training in the future.